1967
DOI: 10.1002/polc.5070170117
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropy of electrical conductivity in doubly oriented nylon 66

Abstract: The electrical conductivity of doubly oriented nylon 66 has been studied as a function of direction over the temperature range 23–150°C. Measurements were made (a) along the chain axes, (b) along the hydrogen‐bonded planes perpendicular to the chain axes, and (c) perpendicular to the hydrogen‐bonded planes. A complicated dependence of conductivity on pretreatment was found. In general the conductivity over the whole temperature range was anisotropic, being least along the chain axes and, after a number of ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1975
1975
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Such as Seanor [1,2] has reported that in nylon 6-6, above 120 8C, there is an ionic conduction while below and at least upto 80 8C it is electronic. In PVC, electronic conduction is reported by Flemming and Renicar [3] whereas Kosaki [4] favors hoping ionic mechanism.…”
Section: Introductionmentioning
confidence: 97%
“…Such as Seanor [1,2] has reported that in nylon 6-6, above 120 8C, there is an ionic conduction while below and at least upto 80 8C it is electronic. In PVC, electronic conduction is reported by Flemming and Renicar [3] whereas Kosaki [4] favors hoping ionic mechanism.…”
Section: Introductionmentioning
confidence: 97%